2021
DOI: 10.7759/cureus.20808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotic Lactobacillus salivarius on Peri-Implantitis Pathogenic Bacteria: An In Vitro Study

Abstract: BackgroundVaried treatment modalities have been described in the past for the management of peri-implant diseases but the evidence of the use of probiotics for the treatment of peri-implantitis is limited. The aim of this study was to determine the antagonistic growth effects of Lactobacillus salivarius on the growth of periimplantitis pathogens. Material and methodAn in vitro assessment of probiotic L. salivarius on peri-implantitis pathogens was done using the serial tube dilution method. Minimum inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In our study, the strong bacteriostatic activity of L. salivarius supernatant and L. agilis supernatant were verified. In agreement, L. salivarius and L. agilis 32 were previously proved to present an excellent antibacterial effect on pathogenic bacterium of humans or chickens ( 25 , 30 ). These implied that the stimulation from gut flora to ISCs was alleviated after feeding L. salivarius or L. agilis .…”
Section: Discussionsupporting
confidence: 62%
“…In our study, the strong bacteriostatic activity of L. salivarius supernatant and L. agilis supernatant were verified. In agreement, L. salivarius and L. agilis 32 were previously proved to present an excellent antibacterial effect on pathogenic bacterium of humans or chickens ( 25 , 30 ). These implied that the stimulation from gut flora to ISCs was alleviated after feeding L. salivarius or L. agilis .…”
Section: Discussionsupporting
confidence: 62%
“…On the probiotic side, Lactobacillus reuteri is one of the most studied probiotics for potential peri-implantitis treatment [ 22 ]. The probiotic has antagonistic effects on peri-implantitis pathogens [ 22 ], yet, recent metadata analyses demonstrated that the bacterium provides limited benefits to patients with peri-implant mucositis or peri-implantitis [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the probiotic side, Lactobacillus reuteri is one of the most studied probiotics for potential peri-implantitis treatment [ 22 ]. The probiotic has antagonistic effects on peri-implantitis pathogens [ 22 ], yet, recent metadata analyses demonstrated that the bacterium provides limited benefits to patients with peri-implant mucositis or peri-implantitis [ 55 , 56 ]. For instance, Peña et al [ 57 ] tested the use of L. reuteri after mechanical debridement and the use of a0.12% chlorhexidine mouthwash in 50 patients with peri-implant mucositis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptococci also inhibit the first two by producing organic acids, especially lactate [ 105 ]. Aggregatibacter actinomycetemcomitans was resistant at all probiotic concentrations used in the study [ 115 ]. Fortunately, it can be inhibited by Lactobacillus bulgaricus [ 116 ].…”
Section: Oral Microbiota Modulation In Valvular Heart Disease–current...mentioning
confidence: 99%